Effect of inhaled budesonide/formoterol fumarate dihydrate delivered via two different devices on lung function in patients with COPD and low peak inspiratory flow. (July 2022) - Huber, Bärbel; Keller, Claus; Jenkins, Martin; Raza, Abid; Aurivillius, Magnus
Background and aims: Low peak inspiratory flow (PIF) is common following severe exacerbations of chronic obstructive pulmonary disease (COPD). Patients with COPD and low PIF may be at risk of suboptimal delivery of inhaled therapies to the airways, especially when using devices such as dry powder inhalers (DPIs), which require greater inspiratory effort than metered dose inhalers (MDIs). We report the results from a 2-week crossover study evaluating the effects of inhaled dual therapy with budesonide/formoterol fumarate dihydrate with an MDI with a spacer versus a DPI in patients with COPD and low PIF. Methods: This randomized, open-label, two-period (each 1 week in duration) crossover efficacy and safety study included patients with severe-to-very severe COPD and PIF < 50 L/min (NCT04078126). Patients were randomized 1:1 to twice-daily budesonide/formoterol fumarate dihydrate MDI (BFF MDI) 320/10 µg with a spacer for 1 week followed by twice-daily budesonide/formoterol fumarate dihydrate DPI (BUD/FORM DPI) 320/9 µg for 1 week, or the inverse. The primary endpoint was peak change from baseline in forced expiratory volume in 1 s (FEV1 ) within 4 h post-dose following 1 week of treatment. Other assessments included pre-dose lung function, pharmacokinetics, and safety, as assessed by adverse events. Results: The modified intention-to-treat analysis set comprised 30 patients (mean age: 66.9 years; mean baseline FEV1 : 766 mL; mean COPD assessment test score: 22.20). Following 1 week of treatment, both BFF MDI and BUD/FORM DPI improved mean [95% confidence interval (CI)] peak FEV1 4 h post-dose [256 (190, 322) mL and 274 (208, 340) mL, respectively]. No clinically meaningful difference between treatments was observed for any lung function endpoint. There were no unexpected safety findings. Conclusion: Dual therapy with BFF MDI and with BUD/FORM DPI led to improvements in lung function in patients with severe-to-very severe COPD and low PIF.